Pemikiran Teodisi Ibn Arabi Tentang Keburukan - Yoshy Hendra Hardiyan Syah (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2022)
This article discusses Ibn Arabi's theodic thoughts on evil in studying, understanding, and exploring more deeply the case of the Covid-19 virus as the implications of evil. Theodicy is a philosophical problem based on a number of arguments and is accompanied by the arguments of philosophical thought so that it can explain and solve a case proportionally and theodicy is a theme that is often the subject of debate, namely more questions about justice over God's omnipotence. In this research, it is sourced from the literature or literature review as research material and a descriptive study and analysis of Ibn Arabi's theodic thought about evil. Ibn Arabi thoroughly discusses the theodic discussion of evil in his book entitled Futuhat al-Makkiyah and Fushush al-Hikam. The problem of good and bad seems to be consistent with the Wahdat al-Wujud theory, he says in the book Futuhat al-Makkiyah that "God is an Absolute Being who is not limited by anything, and He is actually Pure Goodness, in which there is no evil in Him at all. As He is balanced by absolute absence that is pure goodness in which there is no evil in it." On the status of ugliness in Ibn Arabi's theodicy, that everything that has been willed by God cannot be separated from what is called destiny, such as the outbreak of the Covid-19 Virus. In his book Fusush al-Hikam Ibn Arabi says that, the secret of destiny can only be known precisely by Allah, although living beings may be given some kind of vision of their own destiny, which knowledge itself depends on the inclination to know it.